Analisis Pengaruh Nilai Variasi Temperatur Tempering Baja S50C Sebagai Bahan Pisau Mesin Pencacah Plastik - ariyanto, ariyanto; Yudo, Eko; Nicola, Adyu Arya (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
S50C steel is a steel with a carbon content of 0.497 - 0.53% tensile stress of at least 630 mpa. When viewed from the carbon content of the S50C material, this steel is included in medium carbon steel. The carbon range contained in medium carbon steel is between 0.3%C-0.6%C. The minimum requirement for the amount of carbon in steel that can be hardened is greater than 0.3%. By referring to the amount of carbon contained in S50C steel, it can be said that S50C steel can be hardened process. The hardening process is carried out at a temperature of 800 0 C, a temperature of 840 0 C and a temperature of 8800 C, with cooling media being salt water, oil and seawater. After the hardening process is carried out the tempering process at a temperature of 100 0 C, 200 0 C 300 0 C, 400 0 C and 500 0 C,the whole heating process uses an electric oven. The overall parameters of the hardening process are optimized using the Taguchi method. Obtained optimal parameter values at a temperature of 880 0C with a brine-water cooling medium. The average hardness obtained before the tempering process was 56.84 HRC and the highest tempering result was 55.95 HRC the lowest result was 35.15 HRC.